The person accompanying the hospitalized adult: level of information and expectations - Maria de Nazaré de Oliveira Fraga; Anaíza Diógenes Soares (Rev Rene)
The research aimed the information collection from thoseones who were accompanying the patient had about his hospitalized relative’s illness and about the hospital. Moreover, to find out what they expect from the institution and the health team so that they can contribute to the patient’s physical and psychic well being. The study was accomplished in the period of November 22nd to November 27th, 1996 in a public university hospital, using a questionnaire to collect the data 24 people who were accompanying different patients were interviewed. Most of them were women with a low level of literacy, unemployed, and knew little about the relative’s illness and did not know anything about the hospital’s rules. Besides, they had quite low expectations concerning the attendance, being satisfied as long as their relative was receiving medication, food and clean clothes. We concluded that this is related to the low socioeconomic condition, making people consider the little they receive as good quality assistance.